Synergistic effects of CNT and GO on enhancing mechanical properties and separation performance of polyelectrolyte complex membranes. (5th April 2017) - Wu, Jia-Kai; Ye, Chun-Chun; Liu, Tao; An, Quan-Fu; Song, Yi-Hu; Lee, Kueir-Rarn; Hung, Wei-Song; Gao, Cong-Jie
Abstract: High strength polyelectrolyte complex (PEC) nanocomposite membranes were prepared via synergistic ionic complexation between graphene oxide/carbon nanotubes nanofillers (GO/CNT) and oppositely charged polyelectrolytes of sodium carboxymethyl cellulose (CMC) and poly(2-methacryloyloxy ethyl trimethylammonium chloride) (PDMC). Ultraviolet-visible, Raman spectroscopy and microscopies results demonstrated that the combination of one-dimensional CNTs and two-dimensional GO nanosheets lead to an integrated three-dimensional network through π-π interaction with GO distributed parallel to the surface of PEC membranes. Besides, CNTs and GO nanosheets are tightly encapsulated by PEC matrix through electrostatic interactions. The tensile strength of PEC/GO-CNT nanocomposite membrane containing 3 wt% GO-CNT (1:1, w/w) was 155.4 MPa, showing 2.3 and 1.6 times as high as that of PEC/CNT and PEC/GO membranes, respectively. Moreover, PEC/GO-CNT membranes showed improved separation performance and operation stability with introduction of the three-dimensional network constructed by GO and CNT. Graphical abstract: Highlights: Solution-processable PECs incorporated with CNT and GO were prepared. Synergistic effects on enhancing mechanical property of PECM were achieved. Pervaporation separation index was enhanced by introducing GO and CNT.